Proficiency From Immersion: A Human-Centered Design in Cross-Cultural Surgical Training - Li, Meng; Ganni, Sandeep; Albayrak, Armagan; Rutkowski, Anne F.; van Eijk, Daan; Jakimowicz, Jack (Frontiers in Virtual Reality, 2021)
Ensuring surgeons are well-trained in various skills is of paramount importance to patient safety. Surgical simulators were introduced to laparoscopy training during the last two decades for basic skills training. The main drawback of current simulation-based laparoscopy training is their lack of true representation of the intro-operative experience. To create a complete surgical surrounding, the required amount of resources is demanding. Moreover, organizing immersive training with surgical teams burdens daily clinical routines. High-end virtual reality (VR) headsets bring an opportunity to generate an immersive virtual OR with accessible and affordable expenses. Pilot studies reveal that personalized and localization are key needs of the virtual operating room (VOR). They are therefore key in this study. The focus of this study is exploring the effect of different human factors, such as domain knowledge, culture, and familiarity of VR technologies on the perception of the VOR experience. A human-centered design approach was applied to investigate the presence and usability of a VOR. Sixty-four surgical joined the study in The Netherlands and India. The surgeons were referred to as “experts” and surgical trainees as “novices”. The VOR system we used is composed of a laparoscopic simulator, a graphic virtual OR surrounding, and an Oculus Rift VR headset. Participants conducted the “complete Lapchol” task with the VOR. Afterward, four questionnaires were used to collect subjective ratings on presence and usability. The participant’s qualitative feedback was collected using a semi-structural interview as the final stage. Results showed the surgical knowledge only affected perceived mental demand when using VOR. The cultural difference would alter the rating on the majority of items in these questionnaires. VR experience mainly affected the judgment on presence including “Quality of interface” and “Reversible actions”. The interaction effects between surgical knowledge either with culture difference or with VR experience were obvious. This study demonstrated the influences of cultural differences on the perception of immersion and usability. Integrating immersive technologies such as virtual reality and augmented reality to human-centered design opens a brand-new horizon for healthcare and similar professional training.